Perbandingan Perhitungan Trafik Jam Sibuk CDMA 2000 1x pada BTS Inner City dan BTS Outer City dengan Mempergunakan Metode ADPH, TCBH, FDMH dan FDMP - Eka Wahyudi; Wahyu Pamungkas; Adimawono Basuseno (JURNAL INFOTEL, 2013)
Cellular communication system is a wireless communication system where the subscriber can move within a wide network coverage. Code Division Multiple Access (CDMA) is a multiuser access technology that is each user uses a unique code contained in the access channel in the system. Calculation and determination of peak hours can be done by several methods such as: Average Daily Peak Hour (ADPH), Time Consistent Busy Hour (TCBH), Fixed Daily Measurement Hour (FDMH), Fixed Daily Measurement Period (FDMP). The effectiveness of the channel should be determined by occupancy both at inner city territory and outer city territory location. Using design Erlang (Erl) for supply channel at Base Transceiver Station (BTS) that provided, BTS has a design Erlang of 369,83 Erl at inner city and it has a design Erlang of 241,8 Erl at outer city. Peak hour on the inner city occurred at 12:00 to 15:00, whereas the outer city of peak hour occurred at 18:00 to 21:00. Effectiveness value that determined by operator are : <20% = low occupancy (not effective), 21% to 69% = normal occupancy (effective), and > 70% = high occupancy (very effective). In this case occupancy values obtained in each method is between 21% to 69% which means effective